Estudo do efeito da Alternagina-C, uma desintegrina do veneno de Bothrops alternatus e de um peptídeo sintético derivado de sua estrutura, sobre a expressão de fatores de crescimento, angiogênese e cicatrização de lesão em pele de rato - Sant'ana, Estela Maria Correia (2008)
Angiogenesis and wound repair are mediated by several growth factors that are strictly released. Alternagin-C (ALT-C), a disintegrin-like protein from the venom of Bothrops alternatus induces in vivo angiogenesis as well as the cyclic peptide derived from its primary structure, with the ECD motif (ALT-C PEP). This study investigated the effects of ALT-C and ALT-C PEP on angiogenesis and expression of growth factors in a model of wounded rat skin. The rats were anaesthetized; one cutaneous excision (4 mm diameter) was made on the back of each animal, close to the cervical area. Animals were then divided into 7 groups (five rats/group): control (treated with vehicle); locally treated with 10, 60 and 100 ng ALT-C or 10, 20 and 100 ng ALT-C PEP ALT-C PEP for 1, 3, 5 or 7 consecutive days. At the end of experiments animals were killed, the skin was removed; the cranial portion was used for histological analysis and from the caudal portion; protein were extracted, separated by SDS-PAGE and VEGF, FGF-1, TGFβ1, PDGF, IGF1 e TGFα expression was analyze a by Western blotting. The results show that both, ALT-C and ALT-C PEP induced the formation of new vessels, stimulate collagen synthesis and modulated the expression of growth factors, mainly VEGF and FGF1. The increase in VEGF expression could be detected up to 7 days after injury. FGF1 was also significantly increased, but at a lesser extension than VEGF. In conclusion, we present a protein belonging to the disintegrin group of snake venom toxins stimulates angiogenesis and collagen synthesis in an injured tissue. ALT-C may exert its effects via integrin binding and growth factor modulation. As angiogenesis is an important event for wound healing, ALT-C and ALT-C PEP could be candidates to the development of a new drug for wounded skin repair or regeneration.